Young rumanians do not want to be different. An approach to the study of migration amongst young romanians - Bordonaba, Paloma Crespo (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
This paper is a point of departure for the analysis ofthe migratory flows which concern the youngest emigrants, who have in common with other migrants that they are of age and that they have made their own decision to emigrate and their own migratory project, characteristics which differentiate them from other groups which might seem similar, like the «second generation» orthe non-accompanied minors.The paper is divided in three sections, the aim being to systematize the information collected in interviews with young people between 14 and 25 years during a work camp in Romania.Firstly, we try to define and establish the concept of youth and the necessity to consider the heterogeneity of this concept as an epistemological constant. Secondly, we tackle the experiences of the young interviewees, and in some cases, of their closest relatives.Finally, we will analyze the arguments used by these young people to pestify their choice concerning their migratory project as well as their choice of destination.
Keywords: Migration; Romania; Youth